2002
DOI: 10.1001/archneur.59.7.1099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropathological Characteristics of Hippocampal Sclerosis

Abstract: Our results suggest that HS is a frequent pathologic finding in community-based dementia. Individuals with HS have similar initial symptoms and rates of dementia progression to those with AD and therefore are frequently misclassified as having AD. Our clinical and pathologic findings suggest that HS has characteristics of a progressive disorder although the underlying cause remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
137
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 43 publications
14
137
2
1
Order By: Relevance
“…Although some studies on HS‐Aging explicitly state a sparing of CA2/3 in HS‐Aging diagnosis 16, 17, 24, 27, 31, 55, others include cases which present with neuron loss also in other hippocampal sectors than the CA1 and subiculum 15, 29, 43, 44, 57, 58. Frequently, the term “selective” is used for CA1 neuron loss and gliosis, but how potential lesions in other CA areas are considered is not further specified (for example 2, 7, 26, 35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies on HS‐Aging explicitly state a sparing of CA2/3 in HS‐Aging diagnosis 16, 17, 24, 27, 31, 55, others include cases which present with neuron loss also in other hippocampal sectors than the CA1 and subiculum 15, 29, 43, 44, 57, 58. Frequently, the term “selective” is used for CA1 neuron loss and gliosis, but how potential lesions in other CA areas are considered is not further specified (for example 2, 7, 26, 35).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hippocampal sclerosis of aging (HS‐Aging) is considered as a distinct, dementia‐related pathology 18, 31, 35, 56, 58, neuropathologically characterized by severe neuron loss and gliosis in the CA1 area. The subiculum may be affected, but CA4, CA3 and are CA2 spared 16, 41, 43.…”
Section: Introductionmentioning
confidence: 99%
“…The ABCC9 SNP rs704180 was previously associated with risk for HS-Aging, 24,25 a hippocampal pathology seen in $10-25% of autopsied individuals beyond 80 years at death. 26,[73][74][75] Recently, we found an association between HS-Aging and B-ASC in three separate cohorts, including the NACC data set. 8 Using digital image methods for analysis of arteriolar morphology, we found that HS-Aging cases had larger vessel areas, vessel perimeters, vascular areas, and vessel wall thicknesses compared to non HS-Aging cases.…”
Section: Discussionmentioning
confidence: 99%
“…HS often goes unrecognized as a cause of amnesia and progressive dementia in late life, is often diagnosed as AD, 36,37 and has been reported in 12% of older adults with dementia drawn from a community-based autopsy series. 38 The pathogenesis of HS remains controversial; associations with both vascular and degenerative processes have been observed or suggested. 19,37-40 Our data indicate that in elderly adults with progressive amnesia and hippocampal atrophy, HS should be considered as a possible underlying causative factor, although diagnostic tests for HS are not available.…”
Section: Discussionmentioning
confidence: 99%